Climate impacts on the landings of Indian oil sardine over the south‐eastern Arabian Sea. Issue 1 (28th September 2020) - Hamza, Faseela; Valsala, Vinu; Mallissery, Anju; George, Grinson
Abstract: The landings of Indian oil sardine ( Sardinella longiceps, Clupeidae) along the south‐eastern Arabian Sea are about 43.8% of total Indian oil sardine production. The annual landings of this species exhibit large‐scale variability with prolonged years of surplus or deficit landings without identified reason. Evaluating Indian oil sardine landings along the Kerala coast during 1961–2017 in relation to environmental variations, we have elucidated a putative link between variability in landings versus environmental parameters and climate indices. The variables examined in this study, such as salinity and temperature along with physical indices such as upwelling and mixed layer depth (MLD) of the ocean help to propose a mechanism to temporal variability in the landings of Indian oil sardine. Colder temperature and timely intense upwelling lead to nutrient enrichment in the surface water, which promotes the growth of phytoplankton (chl‐ a ) and thereby food availability to Indian oil sardine are found during years with surplus catch. Less saline surface waters and shoaling of MLD at these times could lead to the aggregation of fish at particular depths and thereby a good catches. The reverse mechanism, such as more surface saline water, warm temperature, downwelling or weak upwelling, and less nutrient enrichment, leads to deficit landings. Further, it was noticed that the Pacific decadal oscillation and Atlantic multidecadal oscillation have a more pronounced impact on Indian oil sardine landings over the coast of south‐eastern Arabian Sea than previously reported ENSO associated impacts. All these point towards climate change implications for the Indian oil sardine fishery.